2019
DOI: 10.1063/1.5068712
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical properties of defective MoSe2 repaired by halogen atoms from first-principles study

Abstract: Using first-principles calculations, we have investigated the electronic and optical properties of MoSe2 with Se vacancies (SVSe, α-DVSe, and β-DVSe) and further repaired by halogen atoms (F, Cl, Br and I). For the MoSe2 with Se vacancies, Cl, Br and I atoms can occupy the Se vacancies and form three bonds with the neighboring Mo atoms, but F atom only can form two F-Mo bonds with the lowest adsorption energies due to its smaller atomic radius. Halogen atoms possess one more electron than Se atom, which result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…If the sample is n-type doped, it may give rise to negative charge accumulation. The additional charge may also come from other defects created in MoSe 2 by the electron beam or adsorption of impurities on these defects, which gives rise to the occupied or partially occupied defect-induced states in the gap.…”
mentioning
confidence: 99%
“…If the sample is n-type doped, it may give rise to negative charge accumulation. The additional charge may also come from other defects created in MoSe 2 by the electron beam or adsorption of impurities on these defects, which gives rise to the occupied or partially occupied defect-induced states in the gap.…”
mentioning
confidence: 99%
“…In general, p-type characteristics are difficult to obtain for these materials, 23) and when Se atoms are desorbed, n-type characteristics are expected to be introduced. 24,25) Based on these results, Schottky barrier at MoSe 2 did not suppress the current compared with the barrier at the WSe 2 , possible band structures for the MoSe 2 (band gap: 1.6 eV) and WSe 2 (band gap: 1.7 eV) regions 26) with PtIr 5 coated tips are shown in Fig. 2(d).…”
mentioning
confidence: 81%
“…Previous density functional theory (DFT) calculations showed that a monoselenium vacancy (V Se ) gives rise to two unoccupied degenerate states near the conduction band minimum (CBM) and one occupied state below the valence band maximum (VBM) in monolayer MoSe 2 . It is worth noting that other defects such as a diselenium vacancy (V 2Se ) and a V Se pair (V Se –V Se ) also result in in-gap states, , but we focus on the effect of V Se due to its predominance (Figure S6). While chalcogen vacancies were previously thought to be responsible for the commonly observed n-type behavior in TMDs, there is increasing evidence that they are in fact deep acceptors (A). Theory shows that V Se is stable in either neutral or negatively charged states: that is, it can accept an electron to compensate the native n-doping.…”
Section: Effect Of Proton Beam Irradiation On Mose2mentioning
confidence: 99%